Application of remote sensing technology in studying the interaction between culture and environment in the Third Pole Region - Lu, Zhang (Frontiers in Environmental Science, 2025)
IntroductionThe interplay between cutture and environment in the Third Pole Region holds profound implications for the region's socio-ecological resilience and long-term sustainability. However, existing research has largely relied onisolated analyses, often constrained by the absence of integrative frameworks capable of capturing the dynamic and interdependent nature of cultural and environmental systems. These conventional approaches frequently overlook the spatial-temporal complexity, synergistic relationships, and feedback mechanisms intrinsic to this interplay, thereby limiting their predictive accuracy and adaptability in addressing emerging challenges.MethodsTo bridge these gaps, we propose the Dynamic Cultural-Environmental Interaction Network (DCEN), a novel computational framework that integrates cultural metrics and environmental variables within a graph-based, multidimensional model. This approach systematically captures bidirectional interactions through coupled nonlinear equations, incorporating spatial and temporal dynamics while accounting for external stimuli and abrupt perturbations. Furthermore, we introduce the Adaptive Interaction Strategy for Cuttural-Environmental Systems (AIS-CES), which enables real-tme optimization of model parameters based on system feedback, ensuring stability, adaptability, and enhanced resilience.ResultsExperimental validation demonstrates that the proposed framework effectively simulates complex cultural-environmental interactions with high predictive accuracy, providing a robust foundation for policymaking, adaptive management, and disaster mitigation in the Third Pole Region.DiscussionBy addressing critical limitations in existng methodologies, this research advances a more holistic and actionable understanding of cultural-environmental dynamics, fostering regional sustainability and socio-ecological harmony.